Formation Testing : Low Mobility Pressure Transient Analysis /: Low Mobility Pressure Transient Analysis. ([2016]) - Chin, Wilson C; Zhou, Yanmin; Feng, Yongren; (Control engineer), Yu, Qiang
No abstract available